Evolutionary success and failure of wildlife conservancy programs - Esther Blanco; Javier Lozano (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2012)
This paper develops an evolutionary bio-economic model for hunting, farming and tourism (non-consumptive and safari hunting) to study the determinants of the prosperity of conservancy programs. The model is inspired in the Conservancy program of Namibia, despite it is of more general applicability to other contexts. We explore the relevance of the design attributes of conservancy programs in their prosperity in the long-run as well as the relevance of variables of the context of application highlighted in empirical literature. In addition, we explore the welfare implications of conservancies for local communities and its compatibility with conservation objectives. We discuss the results of the conservancy model with respect to the benchmark of open access and of compensation policies for agricultural looses out of wildlife.
Keywords: 330; Bioeconomic modeling; Community-based management; Wildlife